Origen y contenido mínimo del derecho constitucional financiero (Tema Central) - Guerra Zúñiga, Eddy María de la (2017)
The duty of contribution to public expenditure is the main object of study of the Constitutional Financial Law. Although the referred duty corresponds originally to the legislator, who is the one obligated by the constitutional mandate to seek wealth and wherever it finds it establishes taxes through the law, this duty has as a final destination the citizens, who in their condition of “taxpayers” are obliged to pay all the taxes established in the law. This relationship between citizens and the State is developed through the bond of a set of principles governing the contribution to public expenditure through which a set of taxpayer rights are born and configured. In that sense, constitutional law is the legal branch that regulates the relationship of duties and rights between the State and taxpayers, a complex legal branch even from the theoretical conception, as well as regulatory environment, since there is no consensus about the level of relationship with other branches such as Administrative Law. This article aims to clarify its epistemological affiliation, clarify the type and level of relationship with other branches of public law, and briefly study its field of action.